Epimecia tekes, a new species from south-eastern Kazakhstan (Lepidoptera, Noctuidae, Oncocnemidinae) - Benedek, Balázs; Babics, János; Volynkin, Anton V.; Saldaitis, Aidas (Zootaxa, 2020)
The Noctuidae fauna of Kazakhstan is species-rich and still poorly studied. During a lepidopterological expedition to Almaty Region in the south-eastern part of Kazakhstan, a single female of an unknown Noctuidae species belonging to the subfamily Oncocnemidinae was collected by the senior author of the present paper. The species resembles externally members of the genus Lophoterges Hampson, 1906, especially Lophoterges fatua (Püngeler, 1904), but examination of its genitalia structure revealed that the species is not only undescribed and remarkably different from all known Lophoterges species, but belongs to another genus, Epimecia Guenée, 1839. Up to date, the genus Epimecia was considered as monotypic (Ronkay & Ronkay 1995; Kononenko 2016) and included only Epimecia ustula (Freyer, 1835), which is widely but disjunctively distributed from south-eastern France through the southern Alps, the Balkans, Turkey, Ukraine, southern European part of Russia and western Kazakhstan to southern Ural, north-eastern Kazakhstan and southern Siberia (Ronkay & Ronkay 1995; Kononenko 2016; Titov et al. 2017). The second, peculiar Kazakhstan species of the genus is described below as new.